Madrasah Teachers’ Self Efficacy on Constructing Literacy-Based Teaching Materials - Asmiyah, Siti; Safriyani, Rizka; Muhtarom, Muhtarom (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2023)
One of the most important teaching tasks is designing teaching materials professionally and accordingly constructed to support the teaching and learning process effectively. Thus, teachers need to be aware of selecting the appropriate material and learning resources for their students. This awareness is called self-efficacy which can be described as a person’s belief in their ability to succeed in a particular situation or task including teaching material preparation. Thus, this present research investigated the level of teachers’ self-efficacy in constructing a literacy-based teaching material. It employed mixed-method research, explanatory- sequential research. The respondents were 69 teachers of Madrasah Ibtidaiyah to Madrasah Aliyah in East Java. Surveys, interviews, and focus group discussions were used to collect data that was analyzed using SPSS 25. Further, the data was also described qualitatively based on the theme made. Then, the result shows the teachers’ self-efficacy in constructing literacy-based teaching material is on the intermediate level. Thus, implications and recommendations are given in this study.